2023
DOI: 10.1021/acs.jafc.2c07046
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of Tea Plants (Camellia sinensis) in Response to Salicylic Acid Treatment

Abstract: Salicylic acid (SA) is an important plant hormone and signal required for establishing resistance to diverse pathogens and plant diseases. The abundant polyphenols in tea plants also defend plants from biotic and abiotic stresses. However, whether exogenous SA would increase the resistance of tea plants to adversity and the relationship between SA and polyphenols are still poorly understood. Here, we carried out SA treatment on tea seedlings and performed transcriptome sequencing. SA treatment inhibited the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Salicylic acid is a kind of phytohormone, which is mainly stored in the form of salicylic acid 2-O-β-glucoside in the plant, and increasing its content is conducive to the promotion of plant growth, and the improvement of the plant’s defense and disease resistance ability ( Berim and Gang, 2022 ; Liu et al., 2023 b). It can be seen that an increase in soil pH favors an increase in the synthesis of salicylic acid in the tea tree, which in turn induces an increase in the resistance of the tea tree, while the synthesized excess salicylic acid is stored in the leaves of the tea tree in the form of salicylic acid 2-O-β-glucoside.…”
Section: Resultsmentioning
confidence: 99%
“…Salicylic acid is a kind of phytohormone, which is mainly stored in the form of salicylic acid 2-O-β-glucoside in the plant, and increasing its content is conducive to the promotion of plant growth, and the improvement of the plant’s defense and disease resistance ability ( Berim and Gang, 2022 ; Liu et al., 2023 b). It can be seen that an increase in soil pH favors an increase in the synthesis of salicylic acid in the tea tree, which in turn induces an increase in the resistance of the tea tree, while the synthesized excess salicylic acid is stored in the leaves of the tea tree in the form of salicylic acid 2-O-β-glucoside.…”
Section: Resultsmentioning
confidence: 99%
“…SA is an important plant hormone for establishing connections between diverse pathogens and plant diseases [ 37 ]. Systemic acquired resistance (SAR) is the most effective method to defend against pathogen infection.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study found that there were five main characteristic hormones that led to key changes in C. equisetifolia leaves due to continuous planting, among which the contents of SAG, OxIAA, tZOG and GA 3 had a decreasing trend with continuous planting number, while the content of ABA presented an increasing trend. Salicylic acid is a plant hormone, which is mainly stored as SAG in plants, and its increased content is beneficial to improve plant growth and enhance its defense and disease resistance [ 44 , 45 ]. OxIAA is an indoleacetic acid oxide, and at its proper concentration, can improve plant growth and photosynthesis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%